TINDAK PIDANA KORUPSI PENYALAHGUNAAN DANA RETRIBUSI SAMPAH DI PERCUT SEI TUAN Studi Putusan No: 94/Pid.Sus.TPK/2022/PN.Mdn - Maghfirah Haitami (Universitas Harapan Medan, 2025)
Corruption is a serious problem that hinders development and harms society. Misuse of waste retribution funds that should be used to improve the quality of waste management services is often allocated in a non-transparent and unaccountable manner, resulting in significant losses for society and the environment. Waste retribution, which should be used to improve the quality of waste management services, is often allocated in a non-transparent and unaccountable manner. This study examines corruption in Indonesia using a normative legal research method, which focuses on the analysis of legal norms governing the eradication of corruption. The implementation of the law often faces various challenges, including the lack of coordination between law enforcement agencies, complex bureaucracy, and the ongoing culture of impunity. This study concludes that the provisions for criminalizing corruption in Indonesia, as regulated in Law No. 31 of 1999, provide an important legal framework for eradicating corruption. The implementation of the corruption law faces various challenges, including the lack of synergy between law enforcement agencies and a complex bureaucracy. Analysis of the misuse of retribution funds shows that Corruption in the management of funds harms society and worsens the quality of public services. The effectiveness of criminalizing corruption requires reforms that include increasing the capacity of law enforcement agencies, strengthening oversight mechanisms, and public education regarding participation in preventing corruption.